(3GdcGaj aj GdWHs ((3ejNGFjd jhMfG GdeGdci GdeJWHH s)
(3ChdgG (B:s
(3eGhVYJg GdadGSaI GdMceGA hGfJNHI GdMceGA dSGOGJgG s
(3BNQgG (B:s
(3efRhY GdQZhIGdTOjOI efg ebOGQ LhRJjf Je GdcJGH GdeHGQc s
(3HgG eG LGA ai ehVhY Gdefis
(3bWYI UZjQI edMbI HcJGH bSWG Hf dhbG ai GdHGgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs